PHYCOLIMNOLOGICAL STUDY ON WATER BODIES OF TWO MAJOR PARKS IN ERBIL PROVINCE (NORTH IRAQ) - Hussein, Rabar Mohammed; Koyun, Mustafa; Sen, Bulent; Sonmez, Feray (Parlar Scientific Publications (P S P), 2019)
The study was conducted in Sami Abdurrahman Park and Shanadar Park, Erbil, (North Iraq); four stations were selected in Sami Abdurrahman Park and four stations in Shanadar Park. Water samples were collected in polyethylene bottles and algal samples were collected in sterile vial of 50 ml. The study was focused on the epipelon and phytoplankton composition during the study period. Water temperature at all stations was ranged from 11-16 degrees C. The results of water sample analysis showed the following records; Electrical conductivity ranged as 295-1370 mu S.cm(-1) and turbidity 7-11 NTU; Total alkalinity, acidity and hardness ranged as follows 196-390, 19.21-15.62, 165 to 220 mg CaCO3 1(-1). Calcium and magnesium ion concentrations ranged between 55-96 and 25-30.13 respectively. Total dissolved solid concentration varied between 329-666 mgl(-1). Hydrogen ion values were noted as 7.97-8.25. Dissolved oxygen concentration and biological oxygen demand changed between 2.61- 4.45 mgl(-1) and 14.64 - 17.41 mgl(-1) indicating slight organic pollution. A total of 32 algal species was identified belong to 20 genera and 5 divisions in algal flora of the parks. Green and blue-green algae appeared to occur with more species and more abundant.
Keywords: North Iraq; Erbil; Sami Abdulrahman Park; Shanadar Park; Algae